2016
DOI: 10.1590/1678-4162-8205
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological analysis and sensitivity profile of Staphylococcus spp. in subclinical mastitis of dairy goats

Abstract: RESUMOA mastite subclínica em caprinos acarreta prejuízos econômicos e riscos à saúde pública. Tendo em vista a necessidade de pesquisas que demonstrem as espécies de estafilococos mais isoladas e os testes de sensibilidade que comparem a resistência entre Staphylococcus coagulase negativa (SCN) e positiva (SCP) de cabras com mastite subclínica, os objetivos do presente estudo foram identificar os microrganismos isolados de amostras de leite de cabras com mastite subclínica, bem como definir as espécies de est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
1
4
0
4
Order By: Relevance
“…xylosus have been commonly isolated from intramammary infections [12,29,30]. The high frequency of S. epidermidis in our study is in accordance with a recent study in Mexico [31] reporting this organism as the main Staphylococcus spp.…”
Section: Discussionsupporting
confidence: 92%
“…xylosus have been commonly isolated from intramammary infections [12,29,30]. The high frequency of S. epidermidis in our study is in accordance with a recent study in Mexico [31] reporting this organism as the main Staphylococcus spp.…”
Section: Discussionsupporting
confidence: 92%
“…None of the three biofilm-associated genes were detected in 14 of the nuc-positive biofilm-producing isolates: S. aureus (6) and CNS (8). Other authors have also reported the absence of bap, icaA, and icaD genes in biofilm-producing S. aureus [24,69,70].…”
Section: Genes Associated To Biofilmmentioning
confidence: 96%
“…In small ruminants, this disease is considered a serious economic issue due to the mortality of lactating females, cost of treatment, reduced milk yield and quality [1,2], as well as a public health concern associated with risk of consumer food poisoning [3,4]. Several pathogens can cause mastitis in small ruminants; however, species of staphylococci are the most frequently isolated microorganisms from goat and sheep milk [2,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Um dos fatores que podem explicar as altas taxas de prevalência de mastite subclínica no rebanho é a alta taxa de patógenos contagiosos, como Streptococcus aureus e Streptococcus agalactiae, que continuam sendo um grande problema na maior parte do país e são responsáveis pela maior parte dos casos de mastite subclínica (Coentrão et al, 2008;Nicolau et al, 1996;Salaberry et al, 2016).…”
Section: Discussionunclassified